The Way to Enhance Quality of Life for Attaining Peace According to the Noble Eightfold Path: A case Study of Camp Son Religious Development Center in Petchabun Province - Junlaphan, Wijit (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
Using qualitative-research by the tools documentation and an in-depth interview, this thesis aims to 1) the way of enhancing the quality of life to attain peace according to the Noble Eightfold Path, 2) the way and means to enhance the quality of life of Camp Son Religious Development Center in Petchabun Province, and 3) analyze the way to enhance quality of life for attaining peace of Camp Son Religious Development Center according to the Noble Eightfold Path. From the analysis, it is found the followings: The way to enhance quality of life for attaining peace of Camp Son Religious Development Center according to the Noble Eightfold Path’ means: the proper way of living life of humans based on necessity in the society which comply to the needed things of body, mind, society and thought by holding on to the principle of sufficiency economy, yielding lots of benefits to the society, helping enhance quality of life of the personnel and ones who come to practice for peace, living simple and easy lifestyle with the holding on to sufficient economy, being unambitious, diligent, sacrificing, having public mind, economizing and being honest, etc. all of which lead to a better quality of life that can be applied in daily life for the benefits of both oneself and others in the same time that will yield a warm and peaceful society in accordance with the Noble Eightfold Path; at present, Camp Son Religious Development Center is a part of Mahachulalongkornrajavidyalaya University. The activities of the Center, as the place for Dhamma lectures, towards the development of the quality of the lives of children, youth, students, teachers and general people are: the organizing of training, practicing the right concentration and Dhamma practice of venerable students, and foreign venerable messengers. Each year there will be a circulation of venerable students in faculties of Buddhism, education, humanity and sociology of Mahachulalongkornrajavidyalaya University to come for studying and practicing Dhamma with various forms of arrangements, for instance, the program of Buddhist youth moral-training, ceremonies on Buddhist special days, acceptance of the five precepts, Dana offering, meditation and listening to Dhamma teaching. The supports of sufficient economy in term of the Noble Eightfold Path: forest growing, farming and gardening help the learners get a variety of knowledge, resulting ones who participate the activities to well understand Buddhist peaceful means and are able to resolve the problem of life quality, and become more perfect humans according to the Noble Eightfold Path.